Community, Use it or Lose it? - Gordon, Ross (Anthropologica, 2012)
This article continues the debate on using the term community in anthropological analysis. The article argues for the usefulness of the term community through a consideration of how some homeless people in Canada are perceived by the "housed community," and how some homeless people perceive their own situation in relation to that of the housed community. The article also argues for consideration of people’s aspiration to join or exit a community as an important concept in understand ing notions of community. It also demonstrates that notions of community can impact social policy.